Karakter Tokoh Dasamuka dalam Pagelaran Wayang Kulit Gaya Jawa Timuran Lakon Sumantri Gugur Dalang Ki Puguh Prasetyo : (Kajian Psikologi Kepribadian Ludwig Klages) - Muhammad Raffi Daffarian; Octo Dendy Andriyanto (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research will focus on one of the original Javanese arts in the form of East Javanese style shadow puppet performance “Sumantri Gugur” puppeteer Ki Puguh Prasetyo as oral literature. Dasamuka's journey in fighting for his love ambition for Dewi Citrawati allows researchers to know more deeply about Dasamuka's personality traits. The aim of this research is to describe the personality structure, mental problems and consequences of the actions of the Dasamuka characters. The theory used in this research is Ludwig Klages' theory of personality psychology. The method used in this research is descriptive qualitative, with video documentation of shadow puppet performance “Sumantri Gugur” puppeteer Ki Puguh Prasetyo which will be broadcast live in 2023 as the main source. The aim of using this method is to be able to present data in the form of descriptions, not in the form of numbers. Data collection was carried out using listening and transcription techniques. The results and discussion of this research are that the character Dasamuka is included in the temperament group sanguinis, with various negative desires to justify various means to fight for an ambition. In order to justify any means, the character Dasamuka will face the consequences of his own actions.